Morphological Assessment of Family Solenidae and Family Pharidae (Bivalvia) from Kuching Bay - Khairunnisa, Bohan (Universiti Malaysia Sarawak (UNIMAS), 2007)
Sarawak razor clam can be found in abundant in Kuching Bay area from August to March annually. Limited studies had been carried out, thus information were patchy with regards to the taxonomy of razor clams in Kuching Bay. This study is designed to asses morphological characters of razor clams in Kuching Bay, leading to proper documentation and validating the scientific name properly to each species. Each razor clam has unique characters regarding pallial line and adductor scar. Some level of variation on morphometric character (TL, TWg, SWg and SWd) were also recorded among species. Data matrix were developed using multistate coding system and binomial coding system and subjected to phylogenetic tree construction. Results revealed that Solen regularis, S. sarawakensis and S. digitalis are closely related to each other (monophyletic) whilst Family Pharidae is a distant relative to the group.